PHOTOSYNTHETIC RESPONSES OF Eucalyptus nitens Maiden AT INITIAL STAGES OF ROOT-ROT INFECTION - Luciasih Agustini; Chris Beadle; Karen Barry; Caroline Mohammed (Indonesian Journal of Forestry Research, 2016)
Root-rots are known to be latent diseases that may be present in plants for an extended period without any noticeable expression of  symptoms above ground. Photosynthetic responses of Eucalyptus nitens saplings artificially inoculated with the root-rot pathogen, Armillaria luteobubalina were examined to characterize the initial stages of  root-rot infection. This paper studies three photosynthetic parameters, i.e. photosystem II yield (Fv/Fm), chlorophyll content and photosynthetic capacity (Amax) for two strains of  A. luteobubalina over a seven-month period. Root systems were either wounded or left intact before inoculation. A significant difference was observed in the Fv/Fm ratio between the uninoculated control and inoculated saplings. Photosystem II yield was considered the most sensitive parameter for the early detection of  root-rot disease. Chlorophyll content and Amax decreased for all trees, including controls, during the period of  the experiment, and most likely reflected host responses to seasonal change rather than treatment effects. Fungal re-isolations from symptomatic roots of  inoculated trees confirmed the presence of  A. luteobubalina. Findings from this preliminary trial indicated that there were detectable physiological changes associated with early infection of  root-rot. However, to detect more widespread physiological changes an experiment  of  longer duration is needed.